2013
DOI: 10.1002/dneu.22055
|View full text |Cite
|
Sign up to set email alerts
|

Integrins regulate centrosome integrity and astrocyte polarization following a wound

Abstract: In response to a wound, astrocytes in culture extend microtubule-rich processes and polarize, orienting their centrosomes and Golgi apparatus woundside. β1 Integrin null astrocytes fail to extend processes toward the wound, and are disoriented, and often migrate away orthogonal, to the wound. The centrosome is unusually fragmented in β1 integrin null astrocytes. Expression of a β1 integrin cDNA in the null background yields cells with intact centrosomes that polarize and extend processes normally. Fragmented c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 88 publications
(155 reference statements)
2
16
0
Order By: Relevance
“…This makes sense because in neurons, myosin-IIB predominates in growth cones (Rochlin et al, 1995). In astrocytes, it has already been reported that inhibition of myosin-II increases migration (Peng et al, 2013) (which we found also in our experiments, data not shown), which supports the idea of an interaction between myosin-IIB and kinesin-12, the depletion of either of which increases migration. Moreover, we found in our present studies that it is within amino acids 743-1333 of kinesin-12 and amino acids 1345-1976 of myosin-IIB that the interaction occurs.…”
Section: Discussionsupporting
confidence: 93%
“…This makes sense because in neurons, myosin-IIB predominates in growth cones (Rochlin et al, 1995). In astrocytes, it has already been reported that inhibition of myosin-II increases migration (Peng et al, 2013) (which we found also in our experiments, data not shown), which supports the idea of an interaction between myosin-IIB and kinesin-12, the depletion of either of which increases migration. Moreover, we found in our present studies that it is within amino acids 743-1333 of kinesin-12 and amino acids 1345-1976 of myosin-IIB that the interaction occurs.…”
Section: Discussionsupporting
confidence: 93%
“…To create a brain ECM‐mimicking hydrogel, we narrowed the ECM Matrisome quantification results to proteins with known interactions with integrin heterodimers . From the pool of proteins present in Figure d,f, integrin‐binding sequences were matched via literature mining to their integrin heterodimer pairs (Tables S2, S4, and S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Astrocytes upregulate integrin receptors which have been linked to the extension of glial processes in development (Hirsch et al, 1994) and to astrocyte polarization (Peng et al, 2013). Astrocytes upregulate integrin receptors which have been linked to the extension of glial processes in development (Hirsch et al, 1994) and to astrocyte polarization (Peng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Osteopontin (OPN) is a multifunctional matricellular glycoprotein implicated in a variety of proinflammatory (Chabas et al, 2001) as well as neuroprotective (Meller et al, 2005;Schroeter et al, 2006) and repair-promoting (Suzuki et al, 2010;van Velthoven et al, 2011) effects in CNS injury. Interestingly, OPN is a ligand for integrins (Ellison et al, 1998;Ruoslahti and Pierschbacher, 1987), which are implicated in astrocyte polarization (Peng et al, 2013). Interestingly, OPN is a ligand for integrins (Ellison et al, 1998;Ruoslahti and Pierschbacher, 1987), which are implicated in astrocyte polarization (Peng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation